Views on Depression From Traditional Healing and Psychiatry Clinics in Uganda: Perspectives From Patients and Their Providers - Johnson, Laura R.; Chin, Eu Gene; Kajumba, Mayanja; Kizito, Simon; Bangirana, Paul (Journal of Cross-Cultural Psychology, 2017)
In Uganda, depression is a growing concern, yet mental health professionals are in short supply, and help is often sought from traditional healers. To develop an integrated system of care, we must understand sociocultural aspects of depression including beliefs about help seeking and treatment. In a mixed methods study, we used semi-structured interviews and self-report measures to assess depressed patients (N = 30) seeking treatment in traditional healing (n = 15) and psychiatry clinics (n = 15) near Kampala, Uganda. We assessed demographics, symptoms, treatment characteristics, and explanatory models (EMs) of depression (e.g., labeling the problem, cause, impact on life, best type of treatment). We predicted differences across treatment settings. To further explore EMs, we assessed differences in EMs of patients and their providers by interviewing patient–provider dyads (n = 8 dyads). Patients in both settings were similar in demographics, symptoms, perceived cause, seriousness, and impact of depression. However, patients at traditional clinics were more likely to desire herbal remedies, while those in psychiatry clinics were more likely to desire modern medication. Patient–provider dyads also had different treatment beliefs, with patients desiring financial assistance, social support, and medication, and providers more likely to suggest counseling or advice. The study highlights the need to understand diverse beliefs and treatment trajectories in a multicultural context.
Keywords: traditional healing, explanatory model, Uganda, depression, mixed methods